Effects of aqueous extract of seed of Coriandrum sativum on acute pain in mice - AA Taherian; AA Vafaei; A Rashidy-Pour; M Emami-abarghoii; H Miladi-Gorgi; M Jarrahi; H Sadeghi (Institue of Medicinal Plants, ACECR, 2005)
Background: Since use of synthetic drugs for relief of pain has many side effects, today medical plants are becoming more prominent as substitute therapeutic agents. Previous findings indicate that Coriandrum sativum (CS) modulates pain in both animal and human. Objective: The present work investigated the effects of CS seed on acute pain using hot plate and tail flick models. Method: Albino mice (25-30 g) were used for this study. Aqueous extract of CS seed was injected in doses of 100 and 200 mg/kg 30 min before test. The analgesic effect of the drug on acute pain was evaluated using Hot plate and Tail flick models. Results: Results indicated that CS has analgesic effect in both doses in both models and higher dose of the drug was more effective (p<0.01). Conclusion: The findings above showed that CS could modulate acute pain. Further research is required to determine the mechanisms by which CS has an inhibitory effect on pain sensation.